Comparative Analysis of Implementation Targets of National Projects in Developed Countries Managing Socio-Economic Indicators in Russia - BONDARENKO, Tatiana Grigorievna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article presents an analysis of the implementation of national projects in development of economically advanced countries, which aim to guarantee the socioeconomic development of the countries in the international aspect. The main components of any national project are configured as a strategic development program. As a result of studying the structure of the objectives, certain successes were revealed that were not planned in their national projects. It is proposed to recommend a review of the planning and implementation approaches of national projects in the Russian Federation in terms of the use of the best practices from other countries. RESUMEN El artículo presenta un análisis de la implementación de proyectos nacionales en países desarrollados y económicamente avanzados, que tienen como objetivo garantizar el desarrollo socioeconómico de los países en el aspecto internacional. Los principales componentes de cualquier proyecto nacional de un país se configuran como un programa de desarrollo estratégico. Como resultado del estudio de la estructura de los objetivos, se revelaron ciertos éxitos que no fueron planeados en sus proyectos nacionales. Se propone recomendar la revisión de los enfoques de planificación e implementación de proyectos nacionales en la Federación de Rusia en términos del uso de las mejores prácticas de otros países.